HIV/AIDS Support and African Pentecostalism: The Case of the Redeemed Christian Church of God (RCCG) - Adogame, Afeosemime U. (Journal of Health Psychology, 2007)
International and African discourses on the HIV/AIDS pandemic and intervention neglect the role of religion and religious organizations. Social science perspectives in tackling health and disease neglect religious doctrines and faith central to worldviews and praxis of religious groups. Both aspects are important for religious groups and individuals affected by HIV/AIDS. Informed by a religious studies paradigm and through the religious ethnography of the Redeemed Christian Church of God (RCCG) in Nigeria and the Diaspora, this article demonstrates mechanisms employed by African Pentecostals to combat the epidemic and provide support for infected members. The RCCG conceptualization of disease and healing is central to understanding responses and measures in combating HIV/AIDS.
Paid
Keywords: AIDS; DISEASES; HEALING – Religious aspects; HIV infections; HIV/AIDS; NIGERIA; PENTECOSTALS; Pentecostalisin; RELIGIOUS aspects; healing; religion; theotherapy